Μεταβλητότητα των τιμών της ακίνητης περιουσίας στην Ελλάδα - Συκή, Αικατερίνη (Πανεπιστήμιο Πελοποννήσου, 2022)
The real estate market is characterized by particular economic instability and influenced by a number of factors, also unstable and of a different nature. As an important aspect of human culture, it is inextricably linked to the economy of each region and is an economic indicator of prosperity and well-being, as well as a determining factor in the standard of living of a society. Understanding the behavior and trends of the real estate market can provide suggestions not only for interested buyers, but also for market researchers and those responsible for making decisions regarding the real estate market, city planning and urban development. Factors that affect land and real estate prices are numerous and depend on a number of variables, are directly or indirectly related to each other and constantly interact. It is thus understood that their modeling is a rather complex process, which requires their detailed study. In the context of this dissertation, the analysis of - Volatility of real estate prices in Greece is studied. In order to be able to capture and analyze price volatility in the present work we will use econometrics that combines economic theory, mathematics and statistics in order to measure economic quantities and to compare various economic theories with the relevant empirical data. The final goal of the work is to answer the question, whether the Volatility of real estate prices is done in accordance with the prevailing land use regulations or the land uses are subsequently developed based on the value of the land. Also, the factors that influence and shape this relationship of influence should be taken into account.
Volatility of real estate prices in Greece
Μ.Δ.Ε. 38
Keywords: Ακίνητη περιουσία; Οικονομετρία; Ακίνητη περιουσία; Μεταβλητότητα τιμών